Static and dynamic analysis of FDM printed lattice structures for sustainable lightweight material application. (2018) - Azmi, Muhamad Syafwan; Hasan, Rafidah; Ismail, Rainah; Rosli, Nur Ameelia; Alkahari, Mohd Rizal
This study investigated the effect of strut diameter size of fused deposition modelling (FDM) printed lattice structure on compressive performance and its relation to dynamic behaviour of the lattice structure using vibration analysis. The lattice structure samples were fabricated using FDM 3D printing/additive manufacturing (AM) technique with three sizes of strut diameters: 1.2 mm, 1.4 mm and 1.6 mm. Findings from compression test showed that increased in size of strut diameter would increase the compressive strength performance as well as better energy absorptions. Similar increased trend was shown in the vibration analysis as the strut diameter size increased. This study provides information that lattice structure is suitable for use in dynamic load bearing applications.